LIFE MAPS – AN INTERVENTION TECHNIQUE IN CLINICAL SOCIAL WORK (Annual of the Faculty of Philosophy in Skopje, 2009)
Life maps ate therapeutic technique in clinical social work that gives direction to the individuals or groups to focus on their life in the past, present or future with perspective on their own life, others, own problems and abilities. By using this technique, client answers on the following questions: Who am I?; Where do 1 come from?; Where I go?; How will I get there?; What kind of help do I need?Unfortunately, the use of the life maps in clinical social work is not researched filed yet, which is a serious problem, considering its values as a therapeutic instrument.